Nutritional profile and potential of tempeh flour and date seed flour as mixed complementary foods for chronic malnourished children - Ratnayani Ratnayani; Ade Chandra Iwansyah; Tri Ardianti Khasanah; Dini Ariani; Ervika Rahayu Novita Herawati; Raden Cecep Erwan Adriansyah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Malnutrition has been increasingly linked to imbalances in the composition of gut microbiota. Disruptions in the microbiota can impair nutrient absorption, promote inflammation, and affect immune function, contributing to the development and persistence of malnutrition. Therefore, food intake that can maintain gut microbiota, such as tempeh and dates, is required. The purpose of this study was to characterize the nutrient content of tempeh and date seed flour. This study used an experimental design conducted from August to October 2024. The samples included tempeh and date seed flours boiled for 10 (A1) and 20 min (A2). The flour was processed using PRTPP BRIN. Data were analyzed using a one-way ANOVA test and a post-hoc Duncan test. The results showed a significant difference in the nutritional content of tempeh and date seed flours (p<0,01). Tempeh flour contained 48,11% protein. In contrast, date seed flour had a high dietary fiber content of 82,13% for A1 and 77,59% for A2. In conclusion, both flours have their own nutritional content, namely as a source of protein (tempeh flour) fiber (date seed flour). These findings suggest that tempeh and date seed flour have potential as complementary foods to support the gut microbiota and improve nutritional intake in malnourished individuals.